Hành động ngôn ngữ trì hoãn trong Tiếng Việt (Trên cứ liệu các tác phẩm của Vũ Trọng Phụng, Ngô Tất Tố và Nam Cao) =Delaying language action in Vietnames ( On the evidence of the works of Vu Trong Phung, Ngo Tat To & Nam Cao) /Lê Thị Hiền. - Lê, Thị Hiền.
From the applying of action language theory and conversation theory, delaying language action has been clearly identified and categorized. We hope that these identification and classification will contribute to the deeper analysis of delaying language action with related issues such as: narration, point of view and delaying culture of Vietnamese.